2021
DOI: 10.3389/fphys.2021.737481
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium butyricum Supplement Can Ameliorate the Intestinal Barrier Roles in Broiler Chickens Experimentally Infected With Clostridium perfringens

Abstract: Necrotic enteritis (NE), caused by Clostridium perfringens, is an economically important disease in the broiler. Among normal flora in the broiler intestinal region, Clostridium butyricum has been identified as a probiotic agent that reduces the susceptibility of broilers to C. perfringens. However, the effects of C. butyricum supplement on broiler intestinal integrity during NE are largely unknown. In this study, we investigated the effects of C. butyricum on the growth performance, intestinal morphology and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…It was found that both inflammatory mediators and cytokines result in abnormal expression of tight junction proteins such as ZO-1, claudin-1, and occludin, elevating intestinal mucosal permeability and impairing intestinal barrier function [ 46 , 47 , 48 , 49 , 50 ]. It was shown that CCP infection of broilers resulted in significant downregulation of tight junction proteins, causing intestinal damage in broilers [ 51 , 52 ]. In the present study, the mRNA levels of ZO-1, claudin-1, claudin-2, and occludin in the jejunum were significantly downregulated in CCP-infected broilers, which suggested that the jejunal barrier is impaired in CCP-infected broilers.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that both inflammatory mediators and cytokines result in abnormal expression of tight junction proteins such as ZO-1, claudin-1, and occludin, elevating intestinal mucosal permeability and impairing intestinal barrier function [ 46 , 47 , 48 , 49 , 50 ]. It was shown that CCP infection of broilers resulted in significant downregulation of tight junction proteins, causing intestinal damage in broilers [ 51 , 52 ]. In the present study, the mRNA levels of ZO-1, claudin-1, claudin-2, and occludin in the jejunum were significantly downregulated in CCP-infected broilers, which suggested that the jejunal barrier is impaired in CCP-infected broilers.…”
Section: Discussionmentioning
confidence: 99%
“…Cao et al ( 28 ) found that broilers fed with C. butyricum exhibited an increased VH and a decreased CD in the ileum. Furthermore, a recent study revealed that the addition of C. butyricum to the diet of broilers infected with Clostridium perfringens increased their intestinal VH/CD and ameliorated the degree of their intestinal damage ( 29 ). In the present study, we discovered that C. butyricum considerably improved the duodenal VH and jejunal VH and VH/CD of the broilers, indicating an improvement in intestinal morphology.…”
Section: Discussionmentioning
confidence: 99%
“…Probiotics exhibit positive effects on gastrointestinal morphology and the environment, increase meat quality, and produce numerous metabolites that support the animal’s immune system and growth performance; they also guard against bacterial and zoonotic infections [ 19 , 20 ]. C. butyricum is a widely studied probiotic and is of increased interest in poultry production [ 21 , 22 , 23 ]. Previously, we isolated a C. butyricum strain from cattle feces and found that it could improve broilers’ liver antioxidant capacity, meat quality, and fatty acid composition [ 24 ].…”
Section: Discussionmentioning
confidence: 99%